Plastic Recovery and Utilization: From Ocean Pollution to Green Economy - Adelodun, Adedeji A. (Frontiers in Environmental Science, 2021)
Due to their numerous merits (such as high durability, diverse applicability, ready-availability, low-cost, reusability, and so on), the presumably inevitable use of plastics makes their waste ubiquitously dispersed in our environment. The environmental damage posed, especially to the ecosystem, initiated the need for recourse control of these environmentally refractory pollutants. In this review, the various sources, classifications, fate, and control measures of plastic wastes were appraised. Further, of the three primary techniques for resource control, pyrolysis was reviewed in-depth, showing its relevance and superiority over others. Specific case studies showed that liquid and gaseous fuels derived from pyrolyzed plastics are a waste-to-wealth system that requires optimization and intensification. Such an approach would further help rid our planet of the numerous plastic wastes while improving our economy and achieving our energy demand. One approach identified to improve the current pyrolysis technology is catalysis. Further research should devise green methods for organic catalysis, which are environmentally benign.